2021
DOI: 10.1371/journal.pone.0259652
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis, dental plaque, and atrial fibrillation in the Hamburg City Health Study

Abstract: Background/Aim Atrial fibrillation (AF) is a major health problem and causes heart failure and stroke. Pathophysiological mechanisms indicate a link with oral health including periodontitis (PD), but supporting data are scarce. The aim was to investigate the link between features of oral health and the prevalence of AF. Methods This cross-sectional analysis of the Hamburg City Health Study included 5,634 participants with complete data on their PD and AF status. AF was assessed via self-reported questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…The sample sizes of the abovementioned study population ranged from 227 to 3,056,291, with follow-up periods ranging from 18 months to 17 years. A cross-sectional study, including 5,634 participants with complete data on periodontitis and atrial fibrillation, was conducted to assess the relationship between periodontitis and its severity and atrial fibrillation [ 19 ]. Specific baseline data included in the literature are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The sample sizes of the abovementioned study population ranged from 227 to 3,056,291, with follow-up periods ranging from 18 months to 17 years. A cross-sectional study, including 5,634 participants with complete data on periodontitis and atrial fibrillation, was conducted to assess the relationship between periodontitis and its severity and atrial fibrillation [ 19 ]. Specific baseline data included in the literature are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported the different effects of PD severity on the occurrence risk of atrial fibrillation [ 12 , 19 ], involving healthy patients and mild PD patients (4,588 patients), moderate PD patients (5,197 patients), and severe PD patients (2,382 patients). The prospective cohort study [ 12 ] by Sen et al included healthy individuals, mild PD, moderate PD, and severe PD patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study that monitored patients for 17 years found an increased incidence of AF and stroke with periodontitis, 21 and another study in Hamburg assessed 5,634 participants with AF for severity of periodontitis had found an increased association before adjusting for confounders. 22 Current reviews have suggested the importance of prospective clinical studies to investigate a possible link further. 23,24 Recently, there has been evidence that opportunistic screening for AF may prove bene cial.…”
Section: Introductionmentioning
confidence: 99%